Addition of Papaya Leaf Flour (Carica Papaya) in Feed to Feed Consumption, Daily Body Weight Gain and Feed Conversion for Superior Kampung Chicken, Balitnak - Yuliana Friska; Novi Eka Wati; Miki Suhadi (Formosa Journal of Multidisciplinary Research, 2022)
The aim of the study was to know the effect of papaya leaf flour (Carica Papaya) as an additional feed in the superior village chickens for balitnak feed on daily body weight gain and fee conversion. The experiment used 80 superior five week old native chickens. They were fed control diet + 0% papaya leaf meal (P0), control diet + 10% papaya leaf meal (P1), control diet + 11,5% papaya leaf meal (P3) for 30 days. The control feed contained 21% crude protein and energy metabolism of 3000 kcal kg. The study used a quantitative method with a completely randomized design with 4 treatments and replications. The results showed that the ration had an effect (P>0,05) on feed consumption. The coclusion of the study showed that the addition of papaya leaf flour contect (Carica Papaya) up to 13% as a feed additive in high-yielding native chickens had no effect on daily body weight gain and fedd.